The Influence of Service Quality and Product Quality on Customer Satisfaction in Shopee Cosmetic E-Commerce Online Sales - Januardi Sidauruk; Rossanty , Yossie (Journal of Management, Economic, and Accounting, 2025)
This study aims to analyse the effect of service quality and product quality on customer satisfaction in online sales of Shopee e-commerce cosmetics. The method used in this research is a quantitative method with a survey approach through a questionnaire to 100 respondents. The data analysis technique uses multiple linear regression with the help of SPSS. The results showed that service quality and product quality have a positive and significant influence on customer satisfaction. Product quality has a more dominant influence than service quality. The implications of this research provide insight to sellers in e-commerce to improve product quality and service to increase customer satisfaction.